Effect of Micro-Credit for Poverty Alleviation on Income Growth and Poverty Alleviation—Empirical Evidence from Rural Areas in Hebei, China - Shuangming Yin; Xiaojuan Chen; Xiangyu Zhou; Chao Chen; Jianxu Liu (Agriculture, 2023)
Micro-credit for poverty alleviation is an important financial measure of targeted poverty reduction and rural revitalization in China. This paper employs the OLS model and Logit model to empirically test the effect of micro-credit for poverty alleviation on the income level and stability of income growth of farmers based on the field survey data of 458 registered poverty-stricken farmer households in Fuping County and Quyang County of Hebei Province. The results suggest that micro-credit for poverty alleviation can increase farmers’ income, stabilize the growth of their income, and exert significant short-term and long-term effects on income growth and poverty alleviation. The specialized farmer cooperatives, the scale of production and operation, the proportion of family labor force, and the education level of the head of the farmer’s household exert a significantly positive effect on the farmers’ income and the stable growth of their income. There is a significant interaction between micro-credit for poverty alleviation and specialized farmer cooperatives. The physical conditions of family members exert a negative effect on the stable growth of their income, and other financing channels have no significant effect.